The tragic Turn: from Don Carlos to Wallenstein - Salmerón Infante, Miguel (Escritura e Imagen, 2021)
The stage between completing Don Carlos (1787) and Wallenstein (1799) was the most important one in Friedrich Schiller’s intellectual and creative evolution. This writer stopped writing drama at that moment, as well as read Kant’s three Critiques and began a strong and fruitful friendship with Goethe. The French Revolution exerted a remarkable influence upon Schiller. This shock led him to reject political solutions to suppress despotism and made him to create his concept of aesthetic education. However, this article, apart from the above mentioned reasons, focuses attention on two other aspects, which appear at the beginning and end of an itinerary, namely: the shock caused by Schiller’s creation of Marquis de Posa as a character, and the deep change in his notions of the tragic and tragedy as a writer, which, as being developed in his theoretical works, appear in an original and disturbing way in Wallenstein.